THE CURRICULUM MANAGEMENT GUIDELINE FINE MOTOR DEVELOPMENT OF SPECIAL NEEDS STUDENT IN NAKHON SI THAMMARAT SPECIAL EDUCATION CENTER - Klangsup, Rada; Weeraponkan, Boonlert; Yotharak, Maliwan (Journal of MCU Nakhondhat, 2023)
The objectives of this research are:1) To study the condition of the curriculum administration of Nakhon Si Thammarat provincial special education center. 2) to study the curriculum administration guidelines to promote fine motor development for children with special needs. 3) to presentthe curriculum administration guidelines to promote fine motor development for children with special needs. This research is qualitative research. The data were collected through in-depth interviews with 15 people. 5 key informants and a focus group of 7 experts. The statistic used content analysis.The resultsshowed that1. The curriculum administration conditions of Nakhon SiThammarat special education center have a curriculum drafting process that covers learner disabilitiesconsisting of curriculum administration and curriculum assessment to be used in teaching and learning for learners to have an individual potential2. The curriculum administration guidelines promote fine motor development for children with special needs.It was found that it consisted of principles and reasons,objectives of the guidelines, operational guidelines,monitoring, and evaluation. And there are 3 steps in curriculum administration: 1) Drafting an educational institution’s curriculum that is consistent with the guidelines for promoting small muscle development. 2) Curriculum management that is consistent with the guidelines for promoting small muscle development. 3) Assessment of the curriculum that is consistent with the guidelines for promoting the development of small muscles.3. The experts verifiedthe curriculum administration guidelines promote fine motor development for children with special needsand found that regarding the focus group discussion, the guidelines have suitable, possibility, and usefulness which can be applicable. According to 3 curriculum administration components: 1) Drafting an educational institution’s curriculum that is consistent with the guidelines for promoting small muscle development. 2) Curriculum management that is consistent with the guidelines for promoting small muscle development. 3) Assessment of the curriculum that is consistent with the guidelines for promoting the development of small muscles.